2007
DOI: 10.4143/crt.2007.39.3.109
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Transporter-1 Expression in Squamous Cell Carcinoma of the Tongue

Abstract: Purpose: Tumor cells are known to express hypoxia-related proteins such as glucose transporter-1 (Glut-1). These hypoxia-induced changes may allow tumor cells to survive under sustained hypoxic microenvironments, and the surviving tumor cell under hypoxia may develop a more aggressive phenotype and so result in a poor prognosis.Materials and Methods: The Glut-1 expression was analyzed by immunohistochemistry, and its association with the prognosis was assessed in 60 patients with squamous cell carcinoma of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 13 publications
5
20
0
Order By: Relevance
“…It is believed that GLUT-1 is one of the adaptive strategies that permit tumor growth and progression in an environment characterized by marked oxygenation instability. 12,39 GLUT-1 was expressed in the cytoplasm and membrane of neoplastic cells in 100% of the TSCC cases studied, in agreement with the findings of Kunkel et al 18 and Choi et al, 19 who observed greater membrane and/or cytoplasmic expression in OSCCs. In contrast, Li et al 38 and Ogane et al 40 reported a predominance of membrane expression in head and neck SCC.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is believed that GLUT-1 is one of the adaptive strategies that permit tumor growth and progression in an environment characterized by marked oxygenation instability. 12,39 GLUT-1 was expressed in the cytoplasm and membrane of neoplastic cells in 100% of the TSCC cases studied, in agreement with the findings of Kunkel et al 18 and Choi et al, 19 who observed greater membrane and/or cytoplasmic expression in OSCCs. In contrast, Li et al 38 and Ogane et al 40 reported a predominance of membrane expression in head and neck SCC.…”
Section: Discussionsupporting
confidence: 89%
“…A significant association was observed between the expression of GLUT-1 and the clinical stage. Similar results have been reported by Kato et al 33 for esophageal carcinoma, Choi et al 19 for lip SCC, and Ayala et al 34 for OSCC, highlighting the importance of the association between this immunomarker and tumor stage and its use as a diagnostic and prognostic marker. However, Schrijvers et al 35 found no association between the parameters of clinical evolution and GLUT-1 staining intensity in cases of SCC of the larynx.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, we analyzed the expression level of GLUT1 in 45 cases of TSCC and found that GLUT1 was expressed in all 45 cases. Additionally, the intensity of GLUT1 expression was found to be related to lymph node metastasis and clinic stages, this finding that resembles Choi's results (Choi et al., ). A pertinency between FDG SUV and GLUT1 expression was found in different cancers (Yen et al., ).…”
Section: Discussionsupporting
confidence: 85%
“…In fact, Glut-1 expression has been associated with a poor prognosis in gallbladder cancer [19], oral SC [20], SC of the tongue [21], pancreatic cancer [22], and soft tissue sarcoma [23], and the association between HIF1α and poor prognosis has been reported in breast cancer [24][25][26], nonsmall cell lung cancer [27], nasopharyngeal carcinoma [28], esophageal SC [29], and laryngeal SC [30]. In addition, COX2 expression has been associated with a poor prognosis in laryngeal SC [30] and nasopharyngeal carcinoma [28].…”
Section: Discussionmentioning
confidence: 99%